MySOMOI: An interdisciplinary platform that promotes wholesome oral health - Arzmi, Mohd Hafiz; Shahdan, Intan Azura (University of Malaya, 2018)
On 13th of April, 2018, the constitution of MySOMOI was endorsed during the formation meeting held at the Faculty of Dentistry, University of Malaya which was attended by 29 members from various universities in Malaysia. A Protem Committee was formed on the same day who worked for the registration of the proposed society, subsequently on 17th of July, 2018, MySOMOI was registered as one of the professional body in Malaysia by the Malaysian Registrar of Societies Department. Currently, MySOMOI has more than 50 life members from Malaysia and abroad.